Hajj across empires: pilgrimage and political culture after the Mughals, 1739-1857 - Choudhury, Rishad (Asian connections, 2025)
"A highly original new history of Muslim political culture across the Indian Ocean from 1739 to 1857. Examining South Asian connections with the Middle East, Rishad Choudhury draws on research in multilingual sources and archives to reveal the imperial entanglements of the hajj pilgrimage to Mecca"--